BUILDING SUSTAINABLE BUSINESSES: THE ROLE OF CORPORATE GOVERNANCE EDUCATION - Dixit, Apoorva (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The concept of business sustainability has evolved beyond mere financial performance. In today's world, it encompasses environmental responsibility, social impact, and ethical governance practices. This paper explores the crucial role of corporate governance education in fostering sustainable business practices. We argue that equipping leaders with the knowledge and skills necessary for effective governance is critical for building long-term value for both shareholders and stakeholders. The paper begins by defining corporate governance and outlining the key pillars of sustainability. It then delves into the connection between effective governance and sustainable business practices. Subsequently, the paper examines the need for and benefits of corporate governance education, discussing various approaches for different levels within an organization. Finally, the paper concludes by emphasizing the importance of continuous learning and adaptation in the evolving landscape of corporate governance and sustainability.